PENDIDIKAN EKOPEDAGOGIK UNTUK MENGEMBANGKAN KARAKTER CINTA LINGKUNGAN SISWA SEKOLAH DASAR MELALUI PEMBELAJARAN IPAS - Seran, Eliana Yunitha; Aristo, Thomas Joni Verawanto; Ridwan, Chornelius (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
The background of this research is the interest in efforts to preserve nature and the environment in Kalimantan as an island that has very rich natural potential. Through science subject, elementary school students are intended to have an active role in maintaining, guarding, conserving the natural environment, managing natural resources and the environment wisely. So, through ecopedagogic education, elementary school students can develop the character of the environment care. This research method applied descriptive quantitative survey methods. Data collection tools are questionnaires, observation sheets and interviews. The research subjects were 63 students of class IV at SDN 6 Nanga Nuak, Ella Hilir District, Melawi Regency. Data analysis uses descriptive statistics with percentage formulas. The research results show that the aspect of preparing reading related to the environment for children is 65%, the aspect of making students aware of their relationship with the environment and society is 76%, the aspect of adapting experiences, assignments in class, agreements with the community to turn knowledge into action social, welfare, environmental justice and sustainability 72%, and teaching aspects that link sustainable creatures at 64%. Awareness for the environment when learning science in class is measured by indicators of getting used to throwing rubbish on its place, taking care of plants, maintaining cleanliness, being aware of greenery, tidying up learning equipment.